Attitudes and perceived knowledge of health professionals on the food labelling reform in Israel - Sharon Furman-Assaf; Moran Accos-Carmel; Tatyana Kolobov; Moran Blaychfeld-Magnazi; Ronit Endevelt; Orly Tamir (Cambridge University Press, 2023)
Abstract Objectives: To assess the attitudes and perceived knowledge of health professionals regarding the food product judgemental-labelling reform that began in January 2020 in Israel. Design: Cross-sectional survey. Settings: An online survey among health professionals working in the Israeli health system. Participants: 456 participants (118 physicians, 207 nurses, 131 nutritionists). Results: Most respondents (89·9 %) were women, 36 % had over 20 years of professional experience. All nutritionists, 96·6 % of physicians and 94·7 % of nurses reported hearing about the reform, and most (88·9 % of nurses, 76·3 % of physicians and 75·6 % of nutritionists) claimed supporting the reform to a great or very great extent. Most respondents believe they should discuss issues related to healthy eating with their patients (91·8 % of nurses, 94·9 % of physicians and all nutritionists), but only about half (47·5 % of physicians and 57·0 % of nurses) reported that they have sufficient knowledge in this field, particularly about food labelling. Almost two-thirds of nutritionists (60·3 %) reported instructing patients to change their food intake according to labelling v. 40·1 % and 34·7 % of nurses and physicians, respectively. Only some respondents felt that they could influence their patients' nutrition habits. Most participants believe that additional regulatory measures should also be used to promote healthy nutrition. Conclusions: There is a gap between the desire of physicians and nurses to provide nutritional guidance to the public and their actual knowledge about the labels' meaning as well as their competencies in providing nutrition counselling. When formulating a reform, policymakers should provide clear guidelines about the expectations of implementing it in therapeutic practice.